Diagnosis dan Penatalaksanaan Penyakit Meniere - Opi Akbar; Rossy Rosalinda (Fakultas Kedokteran Universitas Andalas, 2022)
ABSTRACT Background: Meniere's disease is the third leading cause of vertigo after Benign Paroxysmal Positional Vertigo and vestibular neuritis. Meniere's disease is also known as endolymphatic hydrops. Acute symptoms of Meniere's disease are characterized by triad of vertigo, tinnitus and hearing loss. This disease is a challenge for ENT specialist in making a diagnosis and determining the right and optimal management. Objective: Provides knowledge about the diagnosis and management of Meniere's disease, so that it can be handled appropriately. Literature Review: Meniere's disease is an inner ear disorder characterized by spontaneous vertigo attacks, fluctuating low-tone sensorineural hearing loss, aural fullness and tinnitus. The most consistent finding and still being used as the basic mechanism of Meniere's disease to date is the discovery of endolymphatic hydrops. Diagnostic tests to diagnose Meniere's disease include audiometry, glycerol test, caloric test and electrocochleography. Meniere's disease can significantly affect quality of life and generally managed with dietary modifications such as a low-salt diet, medical therapy such as diuretics and surgery such as intratimpani injection and endolymphatic sac surgery. Conclusion: Meniere's disease is characterized by a triad of vertigo symptoms, low-tone sensorineural hearing loss and tinnitus. Making the diagnosis requires a detailed history with a complete audiology and vestibular examination. The management of Meniere's disease consists of dietary modifications, medical therapy and surgery. Keywords: meniere’s disease, endolymphatic hydrops, diuretics, intratimpani injection, endolymphatic sac surgery